PROTOTYPE SMART PARKING AT STMIK AKBA BASED ON MICROCONTROLLER USING RADIO FREQUENCY IDENTIFICATION (RFID) TECHNOLOGY - Ashari, Hilda; M. Yusuf , Andi; Vitalocca, Dyah (Journal of Electrical Engineering and Informatics, 2024)
This study aims to design a prototype smart parking using a microcontroller is expected to provide convenience for parking lot users at STMIK AKBA, making it easier for drivers to find out the availability of parking slots and where the location of the empty slots is in a parking lot and at the same time test the performance of the prototype using RFID. The results of this study indicate that using this system can provide information to parking users quickly and effectively. The results of the implementation of this system can run well based on the results of system testing in its use which get the results of the system's feasibility test with the average time for access takes 3 seconds and the average time for access to exit takes 6 seconds with a suitable category for use.